Combined effect of selected mineral fibres and tobacco smoke on respiratory tract in rats - Hurbánková, Marta; Hraškov, Dominika; Beňo, Milan; Černa, Silvia; Wimmerova, Soňa; Moricová, Štefánia (Central European journal of public health, 2014)
The rats were inhaling amosite and wollastonite fibres at two concentrations (30 and 60 mg/m3) one hour every second day and cigarette smoke of 3 cigarettes per day (with the exception of Saturdays and Sundays). They were sacrificed after 6 month of exposure. Bronchoalveolar lavage (BAL) was performed and selected inflammatory and cytotoxic parameters were examined. Amosite: inflammatory parameters were the most changed after 60 mg/m3 in both groups with or without smoking; the cytotoxic parameters were strongly influenced by smoking. Wollastonite (asbestos substitute) inhalation confirmed lower inflammatory and cytotoxic effects on all examined animal groups in comparison with amosite.
Keywords: silikáty; Male; amositový azbest; mediátory zánětu; Silicates; vztah mezi dávkou a účinkem léčiva; Asbestos, Amosite; Respiratory System; mužské pohlaví; dýchací soustava; Mineral Fibers; minerální vlákna; sloučeniny vápníku; znečištění tabákovým kouřem; krysa rodu Rattus; Tobacco Smoke Pollution; Animals; Calcium Compounds; zvířata; Bronchoalveolar Lavage Fluid; Rats; Inflammation Mediators; bronchoalveolární lavážní tekutina; Dose-Response Relationship, Drug